Design and development of an optimized mixed mode solar dryer - Ahmed Alqadhi, Ahmed Abdullah (2018)
Solar drying is one of the methods that have been used since ancient times. This system has been constantly developed in the last few years to acquire better effective results and drying performance. The efficiency of the performance of a solar dryer is an essentially depends on the thermal distribution and uniformity of flow inside the drying chamber. There are various types of solar dryers have been developed and are classified based on the mode of air circulation (natural circulation and forced circulation), or based on the type of drying such as, direct solar drying, indirect solar drying and mixed mode solar drying etc. Relying on a single mode of these drying system might not provide the optimum results. Therefore, in this study a conceptual design of a mixed mode solar dryer which includes direct, indirect, and forced convection solar drying integrated with desiccant materials is developed and proposed. Some concepts of this design are new and others are inspired from recent works. Based on these, this mixed mode solar dryer is prospective to be superior in the rate of drying as well as air flow uniformity. Moreover, this improved drier which can be utilized for drying the diverse agricultural products is a simple system and might be manufactured locally. Moreover, a simulation of the system using CFD (Computational Fluid Dynamic) software was performed for the optimization of drying chamber configuration before fabrication by predicting the airflow distribution, temperature and velocity profiles throughout the dryer. This simulation process has the capability to resolve equations of mass conversation, energy and momentum utilizing numerical approach and it is a very useful tool to evaluate the temperature and velocity profiles in the various positions of the system and attain a uniform air flow with higher temperature inside drying cell or chamber. In addition, Simulation results are further validated against the experimental work results using data logger (Pico) device to plot temperature profile at diverse positions in the dryer.